Urinary 1-Hydroxypyrene (1-OHP) Analysis Related to Diesel Exhaust on Vehicle Testing Mechanics at Cilincing, North Jakarta, Indonesia - Kurniasari, F; Dian Susanti, T; Mulyana, I; Atmajaya, H; Hikmat Ramdhan, D (KnE Life Sciences, 2019)
Diesel engine exhaust is categorized as carcinogenic to human (group 1) by International Agency for Research on Cancer (IARC) in 2012. Transportation is the biggest contributor of diesel exhaust pollutant. Polycyclic Aromatic Hydrocarbons (PAHs) are the major compound of diesel exhaust that can be found on gas and particle phases. 1-Hydroxypyrene (1-OHP), a metabolite of pyrene, has been used extensively as a biological monitoring of exposure to PAHs. This study aimed to analyze the concentration of urinary 1-OHP related to diesel engine exhaust among vehicle testing mechanics at Vehicle Testing Center Cilincing, North Jakarta. Non-occupational factors such as exposure to cigarette smoke, consumption to grilled food, exposure to open fire, and the presence of pollutant near respondent’s residence are also analyzed. Diesel exhaust exposure was measured by its particle phase, which is personal concentration of PM2.5, PM1, PM0.5, and PM0.25. The subject was 19 vehicle testing mechanics and 18 non-mechanics as the control group. Personal concentration of particulate matter collected using Leland Legacy pump and Sioutas Cascade Impactor and analyzed using gravimetric method. Urinary 1-OHP analyzed using High-Performance Liquid Chromatography with fluorescence detector. Personal concentration of PM2.5, PM1,PM0.5, and PM0.25 are 232.23 µg/m3, 190.58 µg/m3, 164.73 µg/m3, and 140.10 µg/m3. Concentration of urinary 1-OHP ranging from 11.72 to 61.88 µg/or creatinine. The result showed that mean concentration of 1-Hydroxypyrene of mechanic group is significantly higher than non-mechanic group (p=0.001). There is a positive correlation between particulate matter concentration in all size and urinary 1-OHP concentration. There’s no significant correlation between non-occupational factors and urinary 1-OHP concentration. Particulate matter related to diesel engine exhaust is the main contributor of the increase of urinary 1-OHP concentration among vehicle testing mechanics. Keywords: 1-Hydroxypyrene, diesel exhaust, particulate matter, vehicle testing